1999
DOI: 10.4141/a98-107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pasture type on methane production by lactating beef cows

Abstract: . Impact of pasture type on methane production by lactating beef cows. Can. J. Anim. Sci. 79: 221-226. In order to determine the quantity of methane (CH 4 ) produced by lactating beef cows on pasture, 16 Hereford-Simmental first-calf heifers with a mean weight of 511.2 ± 5.8 kg were randomly selected from a larger group of cows (n = 60) on a grazing management experiment and used to evaluate the effects of pasture type on ruminal CH 4 production using the sulfur hexafluoride (SF 6 ) tracer-gas technique. Pastu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
3
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 15 publications
11
88
3
6
Order By: Relevance
“…0.1 for both Spring and Fall). Cow (P 5 0.001) and period (P 5 0.035) effects observed were likely due in part to intake and pasture compositional differences (McCaughey et al, 1999;Pinares-Patino et al, 2007). The average emission of EM (20.85 g kg/DMI) across seasons and treatments is similar to previously reported values (Harper et al, 1999;Grainger et al, 2007).…”
Section: Diet Qualitysupporting
confidence: 83%
“…0.1 for both Spring and Fall). Cow (P 5 0.001) and period (P 5 0.035) effects observed were likely due in part to intake and pasture compositional differences (McCaughey et al, 1999;Pinares-Patino et al, 2007). The average emission of EM (20.85 g kg/DMI) across seasons and treatments is similar to previously reported values (Harper et al, 1999;Grainger et al, 2007).…”
Section: Diet Qualitysupporting
confidence: 83%
“…No change in CH 4 emission has been found with other legumes (see Van Dorland et al, 2007;Hammond et al, 2011) with clover, and in the metaanalysis by Archimède et al (2011), comparing grasses and legumes. A decrease in enteric CH 4 production with high amounts of lucerne was expected based on literature data such as McCaughey et al (1999), who showed that the partial replacement of grasses with lucerne for grazing beef cows decreased CH 4 production per kg DM by 22%. These authors suggested that the lower CH 4 production with lucerne in their trial might have been because of a higher ruminal passage rate with lucerne than with grasses; an increase in ruminal passage rate decreases CH 4 enteric production.…”
Section: Doreau Ferlay Rochette and Martinmentioning
confidence: 86%
“…It has been suggested that feeding lucerne could reduce CH 4 emissions compared with grass. Although no specific effect of legumes was evidenced in a recent meta-analysis on temperate forages (Archimède et al, 2011), a mitigating effect of lucerne on pasture was shown by McCaughey et al (1999) when lucerne partially replaced grasses. The use of lucerne may also lower nitrous oxide emissions through the absence of N fertilisation (Rochette and Janzen, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…According to the prediction model of Benchaar et al (2001), the substitution of timothy hay by lucerne decreases CH 4 emissions by 21% (expressed as % of digestible energy). In a direct comparison, McCaughey et al (1999) observed on grazing beef cattle a 10% decrease in CH 4 production by unit of product when grasses were replaced by a mixture of lucerne and grasses (70 : 30). The authors concluded that this was due to the higher intake observed for lucerne-fed animals, which was related with a higher digestibility rate and an increased passage of feed particles out of the rumen.…”
Section: Mitigation Through Feedingmentioning
confidence: 99%